Does sensitivity to cashflow news explain the value premium on European stock markets? - Thomas Nitschka (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2006)
The decomposition of a European market return into cashflow and discount rate news components suggests that returns on European and country value portfolios react more sensitive to news about the European market returns cashflows than the corresponding growth portfolios. This evidence is substantially weaker when the receptiveness of country value and growth returns to cashflow and discount rate news components of the respective national market return is in question. Moreover, I show that national news series are more important than international news series in explaining the variation in European value and growth returns. Even though European cashflow news play a marginally significant role in explaining returns on value portfolios, there is no persuasive evidence of the notion that high cashflow betas explain relatively high average returns on European countries value portfolios.
Keywords: G12; G15; G14; 519; cashflow and discount rate beta; international stock markets; value premium; book-to-market factor